Endometriosis and the risks of systemic lupus erythematosus and rheumatoid arthritis in the Nurses' Health Study II. Issue 7 (3rd August 2015) - Harris, Holly R; Costenbader, Karen H; Mu, Fan; Kvaskoff, Marina; Malspeis, Susan; Karlson, Elizabeth W; Missmer, Stacey A
Abstract : Objectives: The aetiologies of endometriosis, systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) are all characterised by immune dysfunction. SLE and RA occur more often in women, and reproductive and hormonal factors have been shown to be related to increased risk. However, only one previous study has evaluated the temporal association between endometriosis and SLE or RA. We sought to investigate the association between laparoscopically confirmed endometriosis and subsequently diagnosed SLE and RA. Methods: We analysed data from the Nurses' Health Study II (n=114 453 women) over a 22-year follow-up period. Multivariable, time-varying Cox proportional hazards models were used to calculate HRs and 95% CIs for the association between laparoscopically confirmed endometriosis and confirmed incident SLE or RA. Results: From 1989 to 2011, 103 incident cases of SLE and 390 cases of RA were confirmed. Laparoscopically confirmed endometriosis was significantly associated with subsequent SLE diagnosis (HR=2.03; CI 1.17 to 3.51) and RA diagnosis (HR=1.41; CI 1.05 to 1.89). These associations were robust to adjustment for SLE or RA risk factors and for potential confounders; however, adjustment for hysterectomy and oophorectomy attenuated both relations such that they were no longer significant. No significant differences by infertility status or age (<45 years) were observed. Conclusions: Our findings suggest an association between endometriosis and risk of SLE and RA. It remains to be understood whether and how endometriosis itself, or hysterectomy or other factors associated with endometriosis, is related to risk of SLE or RA.